THE FIRST EXPERIENCE WITH INGARON TREATMENT FOR CONJUNCTIVAL MELANOMA - A. F. Brovkina; Ye. Ye. Grishina; O. Yu. Yatsenko; A. M. Andreichenko (Опухоли головы и шеи, 2015)
The paper describes the first experience with the Russian drug Ingaron from an interferon-group in the treatment of patients with conjunctival melanoma. The positive result obtained during 5-to-62-month follow-ups allows its therapeutic action to be positively appreciated.